2013
DOI: 10.1073/pnas.1313192110
|View full text |Cite
|
Sign up to set email alerts
|

Hippo pathway effector Yap promotes cardiac regeneration

Abstract: The adult mammalian heart has limited potential for regeneration. Thus, after injury, cardiomyocytes are permanently lost, and contractility is diminished. In contrast, the neonatal heart can regenerate owing to sustained cardiomyocyte proliferation. Identification of critical regulators of cardiomyocyte proliferation and quiescence represents an important step toward potential regenerative therapies. Yes-associated protein (Yap), a transcriptional cofactor in the Hippo signaling pathway, promotes proliferatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

34
807
5
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 788 publications
(847 citation statements)
references
References 54 publications
34
807
5
1
Order By: Relevance
“…Elevated levels of TGF-b are associated with both fibrosis and cardiac hypertrophy (33,34). We evaluated signaling through canonical and noncanonical mediators of fibrosis and hypertrophy in response to TGF-b, including ERK, GSK-3b/ b-catenin (35), pSMAD2/SMAD2 (36), Akt (37), and YAP (38). Although we did not observe any robust changes in these effectors, these pathways are known to be activated in the short term in response to pressure overload and remain only moderately elevated at later time points (34,39).…”
Section: Discussionmentioning
confidence: 99%
“…Elevated levels of TGF-b are associated with both fibrosis and cardiac hypertrophy (33,34). We evaluated signaling through canonical and noncanonical mediators of fibrosis and hypertrophy in response to TGF-b, including ERK, GSK-3b/ b-catenin (35), pSMAD2/SMAD2 (36), Akt (37), and YAP (38). Although we did not observe any robust changes in these effectors, these pathways are known to be activated in the short term in response to pressure overload and remain only moderately elevated at later time points (34,39).…”
Section: Discussionmentioning
confidence: 99%
“…The Hippo network has also been implicated in tissue regeneration. Genetically enhanced YAP/TAZ activity in the adult heart stimulates cardiac regeneration after myocardial infarction (Heallen et al 2013, Xin et al 2013. In the intestine, YAP was found indispensable for regeneration of the epithelium by the intestinal stem cells after irradiation (Gregorieff et al 2015).…”
Section: Hippo Pathway: a New Player In Pituitary Stem Cell Regulation?mentioning
confidence: 99%
“…One of the vulnerabilities of the heart is its inability to regenerate, even though heart function and systemic circulation are necessary for life. However, the concept that cardiomyocytes in the adult heart do not proliferate has been challenged by recent studies showing that cardiomyocytes can regenerate through transfer with Yes-associated protein (YAP), a transcriptional co-activator (Xin et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research advances have indicated a central role for YAP in the proliferation, regeneration, and cellsize control of cardiomyocytes (Heallen et al, 2013;Xin et al, 2013;Zhou et al, 2015). In addition to the Hippo kinase pathway that has long been considered the main upstream pathway of YAP, mechanotransduction, which converts mechanical signals from cell-extra cellular matrix (ECM) and cell-cell contact into intracellular signaling pathways via actin tension, has been proposed as another important regulator of YAP (Dupont et al, 2011).…”
Section: Introductionmentioning
confidence: 99%